Low-dimensional material based wearable sensors. (25th November 2021) - Wu, Chenggen; Zhang, Xun; Wang, Rui; Chen, Li Jun; Nie, Meng; Zhang, Zhiqiang; Huang, Xiaodong; Han, Lei
Abstract: Wearable sensors are believed to be the most important part of the Internet of Things. In order to meet the application requirements, low-dimensional materials such as graphene and carbon nanotubes have been attempted to constitute wearable sensors with high performance. Our discussions in this review include the different low-dimensional material based sensors which are employed in wearable applications. Low-dimensional materials based wearable sensors for detecting various physical quantities in surroundings, including temperature sensor, pressure or strain sensor and humidity sensor, is introduced. The primary objective of this paper is to provide a comprehensive review of research status and future development direction of low-dimensional materials based wearable sensors. Challenges for developing commercially low-dimensional namomaterials based wearable sensors are highlighted as well.